2016
DOI: 10.1504/ijebr.2016.074428
|View full text |Cite
|
Sign up to set email alerts
|

Can tolerance of diverse groups improve the wellbeing of societies?

Abstract: People are different, regardless of their assumed similarities, and acknowledging this reality is important for proper communication and interaction. Failing to acknowledge the existence of differences among those with whom we interact could lead to miscommunication, or even conflict in some cases. Thus, a high level of sensitivity is needed to attain sustainable participation in groups and communities, even if those groups or communities are formed by only a few individuals. This paper explores the role of to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Established in the literature is the link between diversity and well-being and includes empirical research that connects workplace gender inequities, positive climate, and well-being; pacific identity and well-being; and less discrimination and more citizen well-being in Europe. The role of ethnic identity and subjective wellbeing were explored in theory (Alnaji, Askari, & El Refae, 2016;Kennedy & Cummins, 2007;Manuela & Sibley, 2014;Miner-Rubino, Settles, & Stewart, 2009). Therefore, I advance based on empirical and theoretical support, Proposition 4: Diversity intelligence is an antecedent to the well-being component of compassionate love servant leadership.…”
Section: Diversity Intelligence and Compassionate Love Servant Leadermentioning
confidence: 99%
“…Established in the literature is the link between diversity and well-being and includes empirical research that connects workplace gender inequities, positive climate, and well-being; pacific identity and well-being; and less discrimination and more citizen well-being in Europe. The role of ethnic identity and subjective wellbeing were explored in theory (Alnaji, Askari, & El Refae, 2016;Kennedy & Cummins, 2007;Manuela & Sibley, 2014;Miner-Rubino, Settles, & Stewart, 2009). Therefore, I advance based on empirical and theoretical support, Proposition 4: Diversity intelligence is an antecedent to the well-being component of compassionate love servant leadership.…”
Section: Diversity Intelligence and Compassionate Love Servant Leadermentioning
confidence: 99%
“…The regression analysis revealed that social tolerance is associated with higher levels of life satisfaction across countries. Consistent with this, Alnaji et al (2016), using data from 108 nations, point out that tolerance toward immigrants and religious views of citizens is positively related to social well-being. In particular, nearly 12% of global variations in well-being are explained by tolerance to immigrants.…”
Section: Introductionmentioning
confidence: 56%
“…Specifically, an establishment of policies and support systems that focus on Mental Health can assist in allowing for creativity, pushing past challenges, and seeking personal growth. In addition to the KBUD framework that recognizes cultural diversity as an indicator that belongs to socio-cultural development [64], research has found that Diversity enhances community well-being and conditions that enable people to live together and that there is a significant relationship between the well-being of a society and tolerance towards diverse groups that exist within the society [141,142]. In this view, Diversity in the context of Maslow's Hierarchy of Needs, is a spatial quality that aids in the satisfaction of self-actualization needs.…”
Section: The Well-being Index In the Context Of Maslow's Hierarchy Of...mentioning
confidence: 99%